Pharmacy practice and policy research in Türkiye: a systematic review of literature - Gizem Gülpınar; Aysel Pehlivanlı; Zaheer- (Taylor & Francis Group, 2024)
Background In recent decades, there has been an interest in clinical pharmacy practice in Türkiye with emerging studies in this area. Despite the recent emergence of diverse pharmacy practice studies in Türkiye, a comprehensive assessment of overall typology of studies and impact has not been conducted thus far.Objectives This systematic review aims to document and assess pharmaceutical policy and practice literature published within the last 5 years in Türkiye. The other aim is to summarise the expected impact of published studies on policy and practice research.Methods The systematic review was conducted according to the guidelines described in the PRISMA Statement. A comprehensive search approach, incorporating Medical Subject Headings (MeSH) queries and free-text terms was employed to locate pertinent literature related to pharmacy practice and policy in Türkiye. The search covered the period from January 1, 2019, to January 1, 2024, and involved electronic databases including PubMed, Medline Ovid, Scopus, ScienceDirect, Springer Link, PlosOne, and BMC.Results In the final grouping, 73 articles met the inclusion criteria and were selected for this review. Among the quantitative studies, majority studies were cross-sectional survey studies. Through the rigorous thematic content analysis seven research domains were developed from the selected literature: drug utilisation and rational drug use, the emerging role of pharmacist, access to medicines and generic medicines, community pharmacy practice, pharmacovigilance/adverse drug reactions, and pharmacoeconomic studies.Conclusions The pharmacist role is evolving; however, several challenges remain in fully realising the potential of pharmacists. These include regulatory barriers, limited public awareness of pharmacists' expanded roles, workforce capacity issues, and the need for ongoing professional development and training. Research studies are needed in the areas of generic prescribing, medicine adherence, intervention studies in community and hospital pharmacy practice, and on pharmacoeconomics and pharmacovigilance.